2019
DOI: 10.1016/j.cmet.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Islet-Resident Macrophages Leads to Inflammation Affecting β Cell Proliferation and Function in Obesity

Abstract: SUMMARY The nature of obesity-associated islet inflammation and its impact on β cell abnormalities remains poorly defined. Here, we explore immune cell components of islet inflammation and define their roles in regulating β cell function and proliferation. Islet inflammation in obese mice is dominated by macrophages. We identify two islet-resident macrophage populations, characterized by their anatomical distributions, distinct phenotypes, and functional properties. Obesity induces the local expansion of resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
277
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(300 citation statements)
references
References 113 publications
(154 reference statements)
20
277
1
2
Order By: Relevance
“…The percentage of F4/80 + positive cells were higher in the db/db islets compared to lean mice at 8, 12 and 16 weeks of age ( Figure 1A, right panel). The observed increase in macrophage numbers in db/db mice was further corroborated with CD68 + immunofluorescence ( Figure 1B right panel), suggesting that macrophages are present at higher numbers in db/db islets which is similar to a recent study showing increased islet macrophage numbers in genetically obese (ob/ob) mice (3). We further performed a sub-population analysis of freshly isolated and dissociated islet cells using flow cytometry with a panel of earlier-identified macrophage markers (23).…”
Section: Higher Numbers Of Macrophages Within Islets Of Db/db Micesupporting
confidence: 89%
See 3 more Smart Citations
“…The percentage of F4/80 + positive cells were higher in the db/db islets compared to lean mice at 8, 12 and 16 weeks of age ( Figure 1A, right panel). The observed increase in macrophage numbers in db/db mice was further corroborated with CD68 + immunofluorescence ( Figure 1B right panel), suggesting that macrophages are present at higher numbers in db/db islets which is similar to a recent study showing increased islet macrophage numbers in genetically obese (ob/ob) mice (3). We further performed a sub-population analysis of freshly isolated and dissociated islet cells using flow cytometry with a panel of earlier-identified macrophage markers (23).…”
Section: Higher Numbers Of Macrophages Within Islets Of Db/db Micesupporting
confidence: 89%
“…We also show that the increased islet macrophage numbers were CD11b + , F4/80 hi , MHCIII + , but lacking Ly6C expression. This islet macrophage phenotype is similarly described in both healthy and obese mice (3,23). The relatively low expression of Ly6C on these cells indicate that these cells were either islet resident macrophages with a self-renewal capacity, or Ly6C + inflammatory monocytes that subsequently shed the Ly6C positivity upon infiltrating the pancreatic islet.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Many studies point to this inflammatory state as an underlying mechanism for the development of insulin resistance in obesity and T2DM. A number of papers have now demonstrated that this chronic tissue inflammatory state also occurs in pancreatic islets [10][11][12] . Islet inflammation has been described in a variety of mouse models of obesity and T2DM as well as in human islets from patients with obesity and/or T2DM 10 .…”
mentioning
confidence: 99%